A simple and convenient approach to fabricate gas permeable mould steel by selective laser melting. (19th September 2022) - Liu, Changyong; Mai, Zhuokeng; Zheng, Chenggang; Zhang, Shengwu; Wang, Pei; Jiang, Mingguang; Liu, Zhiyuan; Lao, Changshi; Chen, Zhangwei
ABSTRACT: Gas permeable steel can extract gases from the mould cavity during the injection moulding process. This study proposed a simple and convenient approach to fabricate gas permeable steel by selective laser melting (SLM). By regulating SLM processing parameters including laser power, scanning velocity and hatch spacing, we tried to seek appropriate parameters for fabricating gas permeable steel. Firstly, the effects of each processing parameter on porosity, pore size and distribution were studied separately. Then, by simultaneously regulating these parameters, the synergistic effects of laser power, scanning velocity and hatch spacing were evaluated. By simultaneously lowering laser power and increasing scanning velocity, samples with the porosity of 20% ~ 30% and gas permeability of 3.54×10 -13  m 2  was obtained and these values are comparable to commercial gas permeable steel. However, the mechanical properties were relatively poor due to the low specific energy and insufficient melting.